Feeding a Modified Fish Diet to Bottlenose Dolphins Leads to an Increase in Serum Adiponectin and Sphingolipids - Sobolesky, Philip M.; Harrell, Tyler S.; Parry, Celeste; Venn-Watson, Stephanie; Janech, Michael G. (Frontiers in Endocrinology, 2016)
Feeding a modified fish diet has been suggested to improve insulin sensitivity in bottlenose dolphins; however insulin sensitivity was not directly measured. Since demonstrating an improvement in insulin sensitivity is technically difficult in dolphins, we postulated that directional changes in the hormone axis: fibroblast growth factor 21 (FGF21)/Adiponectin/Ceramide (Cer), could provide further support to this hypothesis. We measured two hour post-prandial serum FGF21, total adiponectin, % unmodified adiponectin, ceramide, and sphingosine levels from dolphins fed a diet rich in heptadecanoic acid (C17:0) over 24 weeks. Serum FGF21 was quantified by ELISA with an observed range of 129-1599 pg/ml, but did not significantly change over the 24 week study period. Total adiponectin levels (mean ± SD) significantly increased from 776 ± 400 pmol/ml at week 0 to 1196 ± 467 pmol/ml at week 24. The % unmodified adiponectin levels (mean ± SD) decreased from 23.8 ± 6.0% at week 0 to 15.2 ± 5.2% at week 24. Interestingly, although FGF21 levels did not change, there was a good correlation between FGF21 and total adiponectin (ρ = 0.788, P < 0.001). We quantified the abundances of serum ceramides and sphingosines because adiponectin has a defined role in sphingolipid metabolism through adiponectin receptor mediated activation of ceramidases. The most abundant ceramide in dolphin sera was Cer 24:1 comprising 49% of the ceramides measured. Significant reductions were observed in the unsaturated Cer 18:1, Cer 20:1, and Cer 24:1, whereas significant increases were observed in saturated Cer 22:0, Cer 24:0, Cer 26:0. However, total serum ceramides did not change. Significant elevations were detected for total sphingosine, dihydrosphingosine, sphingosine-1-phosphate, and dihydrosphingosine-1-phosphate. Proteomic analysis of the serum proteins revealed few changes in serum proteins over the study period. In conclusion, shifting the dolphin diet to fishes rich in odd chain saturated fatty acids like C17:0 resulted in increased serum levels of the insulin sensitizing hormone adiponectin and serum sphingosines consistent with an insulin sensitizing phenotype. It is still unclear whether FGF21 plays a role in the regulation of adiponectin in dolphins, similar to that shown in laboratory animal models.